2018
DOI: 10.1371/journal.pone.0196236
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cigarillo packaging elements on young adult perceptions of product flavor, taste, smell, and appeal

Abstract: IntroductionProduct packaging has long been used by the tobacco industry to target consumers and manipulate product perceptions. This study examines the extent to which cigarillo packaging influences perceptions of product flavor, taste, smell, and appeal.MethodsA web-based experiment was conducted among young adults. Participants viewed three randomly selected cigarillo packs, varying on pack flavor descriptor, color, type, branding, and warning—totaling 180 pack images. Mixed-effects models were used to esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 51 publications
6
25
0
Order By: Relevance
“…In line with our hypotheses, perceptions of taste, smell, and enjoyment all increased due to characterizing flavors; these results replicate previous findings demonstrating that characterizing flavor descriptors increase appeal ratings (Meernik et al., 2018). We also found support for the prediction that characterizing flavors increase social acceptability as was observed in focus group research (Camenga et al., 2018; Wagoner et al., 2016).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In line with our hypotheses, perceptions of taste, smell, and enjoyment all increased due to characterizing flavors; these results replicate previous findings demonstrating that characterizing flavor descriptors increase appeal ratings (Meernik et al., 2018). We also found support for the prediction that characterizing flavors increase social acceptability as was observed in focus group research (Camenga et al., 2018; Wagoner et al., 2016).…”
Section: Discussionsupporting
confidence: 92%
“…All participants were informed that they would see a series of images of cigarillo flavors and that they must view the images and read the accompanying text, as they would be asked questions about the images later (see Figure 2 for sample images). In order to prevent preexisting biases toward the cigarillo products, we used a fictitious brand, called “Brentfield,” which has been used in previous research (Byron et al., 2018; Lazard et al., 2019; Meernik et al., 2018). Images of all stimuli used in this study can be viewed in the Online Supplementary Materials file.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to research on cigarettes, findings from studies on perceptions of cigar packaging have identified that packaging descriptors and claims (e.g., “natural”) [ 31 , 32 ], branding [ 32 ], price promotions [ 32 , 33 ], and colors [ 31 , 32 , 34 ] are appealing to consumers. Moreover, many appealing cigar packaging characteristics are unique to cigars and not apparent in cigarettes.…”
Section: Introductionmentioning
confidence: 91%